Pengaruh penggantian lemak kakao oleh glukomanan porang dan lesitin terhadap sifat fisik cokelat hitam (Dark chocolate) - Aji Sutrisno; Panji achmad apriyandi (AGROINTEK, 2024)
A Low-fat dark chocolate was developed by replacing cocoa butter with porang glucomannan and lecithin addition. The study was to determine the effect of cocoa butter replacement levels by porang glucomannan (10%, 15%, 20%) and lecithin (1%, 1.5%, 2%) on the melting point, hardness, cohesiveness, springiness , gumminess, chewiness, color, and glossiness of dark chocolate which was using a factorial group randomized design with ANOVA and continued with the Tukey HSD test. The results showed that not interaction of the level of cocoa butter replacement by glucomannan and lecithin on melting point. The cocoa butter replacement level by porang glucomannan and lecithin and their interactions affected hardness, cohesiveness, springiness , gumminess, chewiness, color, and glossiness. The higher level of cocoa butter replacement levels by porang glucomannan and lecithin increased the melting point and hardness of dark chocolate. Porang glucomannan and lecithin can be used to reduce cocoa butter and can improve the physical properties of dark chocolate.